Intelligent Systems for the Internet of Things: Essence, Perspectives and Problems - Mahmudova, Shafagat (International Journal of Natural Sciences Research, 2021)
This article outlines the Internet of Things (IoT). The Internet of Things describes a network of physical objects, i.e., the “thing” including sensors, software, and other technologies for connection and data sharing with other devices and systems over the Internet. In other words, IoT is a relatively new technology enabling many “smart” devices to get connected, to analyze, process, and transfer data to each other and connect to a network. The article clarifies the essence of intelligent systems for the Internet of Things, and analyzes the most popular software for the IoT platform. It studies high-level systems for IoT and analyzes available literature in this field. It highlights most advanced IoT software of 2021. The article also identifies the prospects and challenges of intelligent systems for the Internet of Things. The creation of new intelligent systems for IoT and the development of technology will greatly contribute to the development of economy.